Modes of Retrotransposition of Long Interspersed Element-1 by Environmental Factors - Ishizaka, Yukihito; Okudaira, Noriyuki; Tamura, Masato; Iijima, Kenta; Shimura, Mari; Goto, Motohito; Okamura, Tadashi (Frontiers in Microbiology, 2012)
Approximately 42% of the human genome is composed of endogenous retroelements, and the major retroelement component, long interspersed element-1 (L1), comprises approximately 17% of the total genome. A single human cell has more than 5×105 copies of L1, 80~100 copies of which are competent for retrotransposition (RTP). Notably, L1 can induce RTP of other retroelements, such as Alu and SVA, and is believed to function as a driving force of evolution. Although L1-RTP during early embryogenesis has been highlighted in the literature, recent observations revealed that L1-RTP also occurs in somatic cells. However, little is known about how environmental factors induce L1-RTP. Here, we summarize our current understanding of the mechanism of L1-RTP in somatic cells. We have focused on the mode of L1-RTP that is dependent on the basic helix–loop–helix/per–arnt–sim (bHLH/PAS) family of transcription factors. Along with the proposed function of bHLH/PAS proteins in environmental adaptation, we discuss the functional linking of L1-RTP and bHLH/PAS proteins for environmental adaptation and evolution.